Oral rehydration therapi: sugar-salt solution using special scoop measurement vs glucose-electrolyte solution - Julniar Mawardi; Rusdi Ismail (Paediatrica Indonesiana, 1981)
222 well nourisned children aged between 6 - 24 months suffering from acute diarrhoea in the OPD Department Child Health, Medical School University of Sriwijaya. Palembang since August 1979 until March 1980 were included in the study.They divided into 2 groups, one group receiving ORS with standard formula and the other group receiving sugar salt solution using specific scoop (blue spoon).The conclusion made from this study is that the efficacy of the sugar-salt solution measured by a special scoop (blue spoon) was not significantly different from the glucose-electrolyte solution. Likewe, the side-effects found were similar in those two groups.There are still some constraints made by some experts to use sugar-salt solution for oral rehydration. The result of this study can be used as an addition information to carry out the wider scale of clinical and field trial concerning this sugar-salt solution.